#TITLE_ALTERNATIVE# - HEIDI SAPUTRO (NIM :15112013), REZKY
The physical properties of geothermal manifestations needs to be identified for geothermal exploration activity. One of this physical properties is surface roughness. Surface roughness is the terrain property that most strongly influences the strength of radar backscatter. This research aims to identify the roughness at geothermal manifestations, specifically for altered surface, mud pools, and hot springs using syntethic aperture radar data from Sentinel-1A satellite imagery. A surface roughness measurement at geothermal field using pin meter was used to verivy the estimated roughness. The linear fitting method was used to obtain correlation determination between initial model which is function of wave length, backscattering coefficient, and local incidence angle with surface roughness at field from measurement to make a surface roughness model. The resultant model was applied to map a spatial distribution of surface roughness in the Wayang Windu geothermal field. The result show that in altered surface has a rough surface roughness while mud pools and hot springs has a smooth surface roughness.